Reflection in Action: Strategies for Teacher Self-evaluation : (EFL Teacher Preparedness to Work with Young Learners) - Cirkovic-Miladinovic, Ivana; Dimitrijevic, Maja (Technium Social Sciences Journal, 2020)
Given classroom complexity und uncertainty, teachers face with lots of challenges during their teaching repertoire. They face with specific problems they should respond to and manage so the world of the classroom demands that teachers have practical knowledge that enables them to negotiate the practical problems they face. The fact that reflection in action is a personal, spontaneous, tacit process it means that it limits teachers’ opportunity to seek or receive feedback from others or from the reflective episode itself. Moreover, reflections in action focus on events and situations that arise spontaneously und unplanned (Cochran-Smith & Lytle, 1990). In a real sense, reflection in action is reactive, not proactive. This kind of evaluation has one problematic characteristic: the teacher is both evaluator and evaluatee (Airasian & Gullickson, 1994). Having in mind mentioned challenges for the teacher in the classroom, it would be useful for a teacher to be familiar with some strategies for teacher self-evaluation. The paper presents a study of an online survey to examine teachers’: a) self-efficacy to work with multilingual students in the Serbian YLs classroom, b) received training in the area of teaching young learners, c) beliefs about knowledge, skills and resources needed to work with YLs, d) interest in receiving additional training. The research takes into consideration the specific aspects of students’ L1, i.e. the Serbian language. Findings suggest that while a majority of the teachers has not received specific training on working with YLs, most of the teachers feel somewhat confident about their ability to work with such student populations.